Assessing patient–provider communication barriers to implementing new expert panel risk reduction guidelines. (October 2014) - Kish-Doto, Julia; Moultrie, Rebecca; McCormack, Lauren; Furberg, Robert D.; LaBresh, Kenneth A.
Abstract : The Institute of Medicine's list of 100 priority topics for comparative effectiveness research highlights the importance of translating and disseminating medical information to clinicians and consumers. In line with these priorities, the National Heart, Lung, and Blood Institute supported a study of the Expert Panel on Integrated Guidelines for Cardiovascular Health and Risk Reduction in children and adolescents prior to its release. The primary purpose of the study was to identify implementation of the Guidelines and communication barriers among clinicians who see children. The innovative, evidence-based guidelines encompass the development, progression, and management of 14 risk factors from birth through 21 years of age. A growing body of evidence supports the need for active multifaceted dissemination and implementation support strategies to address chronic health problems. This study qualitatively assessed clinician receptivity to guideline implementation and communication of pediatric cardiovascular risk factors to patients and caregivers using a theoretical framework tailored for clinicians. Results indicated that clinicians were generally receptive to the guideline recommendations but were less likely to implement recommendations associated with counseling patients about certain behavioral risk factors (i.e. nutrition and diet; growth, overweight, and obesity; and physical activity). Strategies to enhance or obtain these skills as part of medical training are needed. Recommendations are provided to address the barriers identified by clinicians in the intervention development phase of this research.